(untitled) (Revista Internacional de apoyo a la inclusión, logopedia, sociedad y multiculturalidad, 2020)
The University is characterized as a space of human formation, being a reference institution in relation to the construction of knowledge, education, technological and social development. In this context, universities obey the inseparability between teaching research and extension; Thus we seek to present the extension project Popular University - UNIPOP that develops activities with the University of the State of Mato Grosso - UNEMAT, Sinop Campus that has consolidated itself as a space of confluence, debate, development, socialization and diffusion of diverse knowledge. The objective is to show the importance of university extension, through extension project actions, aimed at offering short courses in various areas of knowledge. The procedures adopted in this research were subsidized by qualitative methods, to obtain the data, we used an open questionnaire applied to the students who participated in the offered courses. The results point out the importance of extension actions developed by the university for the population in general, being relevant and significant for the construction of knowledge, as well as contributing to the knowledge of the academy to be socialized and the participating public of the taught mini-courses have one more space. that enables to build and consolidate varied knowledge.